Organic black pepper (Piper nigrum) cultivation on Gliricidia standards in coconut (Cocos nucifera) plantations in South Andaman: organic matter production and recycling of nutrients - PANDEY, C B; SINGH, RANJAY K (The Indian Journal of Agricultural Sciences, 2010)
A study was conducted in 2006–07 to estimate on-farm production of organic biomass, its decomposition and nutrient release in coconut (Cocos nucifera L.) – clove (Eugenia cariophyllata Thunb.) – Gliricidia [Gliricidia sepium (Jacq.) Kunth ex Walp.] and coconut–nutmeg (Myristica fragrance Houtt. Nees.) – Gliricidia plantations. The study was ultimately aimed to prepare a balance sheet of availability and demand of nutrients (N, P, K) in the plantations for organic black pepper (Piper nigrum L.) production on Gliricidia grown as standards between 2 coconut trees in South Andaman Island. Total organic biomass (litter) from leaf litter and fine root biomass of coconut, clove and nutmeg, coconut husk and pruning biomass of Gliricidia was 14.9 tonnes/ha/year in coconut–clove–Gliricidia and 14.4 tonnes/ ha/year in coconut –nutmeg – Gliricidia plantation. Decay rate coefficient of most of the organic biomass ranged from 0.0009 to 0.119/day and decomposition time from 15 to 102 days indicating that nutrient release from the organic biomass was annual in the hot humid climate of the Island. The organic biomass together were found to recycle 190 kg N, 13 kg P and 129 kg K/ha/year in the coconut–clove–Gliricidia and 183 kg N, 12 kg P and 122 kg K/ha/year in coconut– nutmeg–Gliricidia plantation. Demand of N, P and K in the coconut–clove–Gliricidia was 191 kg N, 127 kg P and 365 kg K/ha/year, while it was 226 kg N, 129 kg P and 408 kg K/ha/year in coconut–clove–Gliricidia plantation. This indicates that 81–100% requirement of N, 9–10% of P and 30–35% of K can be met by the native trees through organic biomass recycling in the plantations. Organic black pepper production on Gliricidia ranged from 0.8 to 1.6 kg/standard.